2007
DOI: 10.1158/0008-5472.can-06-3633
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Molecular Markers Predicting Sensitivity in Solid Tumors to Dasatinib: Rationale for Patient Selection

Abstract: Dasatinib is a multitargeted kinase inhibitor that was recently approved for the treatment of chronic myelogenous leukemia and Philadelphia chromosome-positive acute lymphoblastic leukemia with resistance or intolerance to prior therapy. It is also in clinical trials for treating patients with solid tumors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
260
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(285 citation statements)
references
References 45 publications
23
260
2
Order By: Relevance
“…Interestingly, dasatinib sensitively did not appear to correlate with the levels of Src activation in each cell line. Consistent with these findings, Src kinase failed to emerge as a marker predicting dasatinib sensitivity in breast cancer cell lines (41,42), underscoring the potential broad target specificity of this tyrosine kinase inhibitor (43,45). Although promising candidates have been identified, the direct mediators of dasatinib action in breast tumor cells remain to be confirmed.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Interestingly, dasatinib sensitively did not appear to correlate with the levels of Src activation in each cell line. Consistent with these findings, Src kinase failed to emerge as a marker predicting dasatinib sensitivity in breast cancer cell lines (41,42), underscoring the potential broad target specificity of this tyrosine kinase inhibitor (43,45). Although promising candidates have been identified, the direct mediators of dasatinib action in breast tumor cells remain to be confirmed.…”
Section: Discussionmentioning
confidence: 70%
“…We investigated the efficacy of the tyrosine kinase inhibitor dasatinib, currently in clinical use for the treatment of patients with refractory leukemias, as a single-agent in our preclinical assays. Although originally designed as a Src kinase family inhibitor, dasatinib appears to have broad tyrosine kinase specificity (43,45) and effectively inhibits breast tumor cell lines with the most aggressive phenotypes (41,42). Likewise, dasatinib suppressed each tumor cell line tested here including HER2Δ16-expressing trastuzumab-refractory tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a baseline pharmacodiagnostic sample would be simpler to obtain from a routine diagnostic biopsy, for example, as opposed to posttreatment (pharmacodynamic) signatures where a separate biopsy procedure would be required. When comparing the pancreas cancer susceptibility gene signature for bosutinib described here to that for breast cancer (18) and prostate cancer (19) with dasatinib, we did not find shared genes. There are several possibilities to explain this difference.…”
Section: Discussionmentioning
confidence: 59%
“…One important preclinical study found a six-gene predictor for dasatinib susceptibility of breast cancer cell lines, and this was associated with a "triple-negative" [estrogen receptor (ER), progesterone receptor (PR), HER2] pattern in archival human breast cancer specimens (18). Another used a panel of prostate cancer cell lines to identify a five-gene set predictor, several of which were down-regulated after dasatinib treatment (19).…”
Section: Introductionmentioning
confidence: 99%